Directional characteristics of a planar annular plate for axially-symmetric free vibrations - W. P. Jr. RDZANEK; Z. ENGEL (Archives of Acoustics)
There is solved a coastal problem of the acoustic wave radiation at Fraunhofer zone for a planar annular plate vibrating harmonically. It is assumed that a plate is clamped with both its banks, inner and outer, into a planar rigid baffle. There is an analysis of axially-symmetric free vibrations. There are directional-frequency characteristics for both kinds of sources - annular plate and annular membrane.